Does prey scarcity increase the risk of wolf attacks on domestic dogs? - Kojola, Ilpo; Hallikainen, Ville; Kübarsepp, Marko; Männil, Peep; Tikkunen, Mari; Heikkinen, Samuli (Zenodo, 2022)
Gray wolf (Canis lupus) predation on domestic dogs (Canis familiaris) is a considerable wolf-human conflict issue in several regions of Europe and North America but has not been well documented in the scientific literature. Livestock depredations by wolves may be related to the abundance of wild prey. Regardless of the presumed motivations of wolves for attacking dogs (likely due to interference competition and predation), the abundance of wild prey populations may also influence the risk of wolf attacks on dogs. We examined whether the annual number of tatal attacks by wolves on dogs was related to the abundance of primary prey, including wild boar ( Sus scrofa ) and roe deer ( Capreolus capreolus ) in Estonia, as well as the abundance of moose ( Alces alces ) in Finland. Statistical models resulted in significant negative relationships, thus providing evidence that the risk of attacks in both house yards (Estonia) and hunting situations (Finland) was highest when the density of wild prey was low. Wild ungulates cause damage to agriculture and forestry, but they seem to mitigate conflicts between wolves and humans; therefore, it is necessary to develop a holistic, multispecies management approach in which the importance of wild ungulates for large carnivores is addressed. Data for roe deer and wild boar exist only for Estonia, data for moose only for Finland Funding provided by: Natural Resources Institute Finland* Crossref Funder Registry ID: Award Number: 41001-00001401